2014
DOI: 10.11646/zootaxa.3812.1.1
|View full text |Cite
|
Sign up to set email alerts
|

<strong><em>Zwicknia </em>gen. n., a new genus for the <em>Capnia bifrons </em>species group, with descriptions of three new species based on morphology, drumming signals and molecular genetics, and a synopsis of the West Palaearctic and Nearctic genera of Capniidae (Plecoptera)</strong>

Abstract: Zwicknia Murányi, gen. n. is erected for the Capnia bifrons species group sensu Zhiltzova, 2001 with the description of three new species based on morphology, mating call, and the mitochondrial DNA marker cytochrome c oxidase I: Z. acuta Murányi & Orci, sp. n., Z. kovacsi Murányi & Gamboa, sp. n. and Z. rupprechti Murányi, Orci & Gamboa, sp. n.. Zwicknia bifrons (Newman, 1838) comb. n. is selected as the type species and redescribed. The other three species placed into Zwicknia, gen. n., Z. sevanica (Zhiltzova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 913 publications
(45 citation statements)
references
References 60 publications
2
42
0
1
Order By: Relevance
“…Plecoptera is thus an efficient taxonomic tool with which to detect the impacts of geographical and climatic changes on the stability of regional biodiversity. Despite the relatively scarce current molecular studies on European Plecoptera do not yet allow evaluating the existence of the enormous cryptic diversity found in some other aquatic organisms33343536, we are aware that the natural diversity of Plecoptera could be larger than predicted from current taxonomical knowledge and the real distribution patterns could be slightly different, and this could lead to potential follow-up studies. Our study not only provides evidence for the profound effects of human-induced global change on regional biodiversity but also illustrates a more complete picture of biodiversity stability in the context of both spatial and temporal scales.…”
Section: Discussionmentioning
confidence: 97%
“…Plecoptera is thus an efficient taxonomic tool with which to detect the impacts of geographical and climatic changes on the stability of regional biodiversity. Despite the relatively scarce current molecular studies on European Plecoptera do not yet allow evaluating the existence of the enormous cryptic diversity found in some other aquatic organisms33343536, we are aware that the natural diversity of Plecoptera could be larger than predicted from current taxonomical knowledge and the real distribution patterns could be slightly different, and this could lead to potential follow-up studies. Our study not only provides evidence for the profound effects of human-induced global change on regional biodiversity but also illustrates a more complete picture of biodiversity stability in the context of both spatial and temporal scales.…”
Section: Discussionmentioning
confidence: 97%
“…n.. For the latter species, we also provide additional details on its intersexual communication signals, which were illustrated and succinctly described as the form 'Cappan' by Rupprecht (1997). Sequences of the mitochondrial gene cytochrome c oxidase I (COI) of these species are analysed together with new sequences of Z. bifrons and Z. rupprechti from western and northern Europe and the data from southeastern Europe published in Murányi et al (2014).…”
mentioning
confidence: 99%
“…The mitochondrial contribution of female A. decepta to A. arapahoe was indicated by the absence of divergence between them, but was moot on whether this was from hybridization, recent divergence, or a faulty taxonomy. In retrospect, the combination in male A. arapahoe of many Arsapnia ‐like anatomical characters (Murányi et al, ) and a relatively long epiproct reminiscent of Capnia gracilaria (and other species of Capnia ; Nelson & Baumann, ) might have been interpreted as evidence of the hybrid origin of A. arapahoe , albeit one difficult to recognize amidst a background of morphological variability (Baumann & Stark, ). Regardless, the rise of genetic and genomic tools has made the detection of hybridization relatively straightforward, which in turn has revealed that hybridization and even hybrid speciation are a regular occurrence among many insect taxa (The Heliconius Research Consortium, ).…”
Section: Discussionmentioning
confidence: 99%